Reactivity of the Reproductive System During Physical Activity (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Hormones play a very important role in the functioning of the human body. These substances stimulate the activity of certain cells and systems of the body. Hormones are produced by endocrine glands and certain tissues. Among the wide range of hormones, anabolic and catabolic hormones are of particular importance. Catabolism is the process of metabolic breakdown of cells and tissues, as well as the breakdown of complex structures with the release of energy in the form of heat or in the form of adenosine triphosphate. Catabolic processes provide a large amount of energy. Anabolic processes are the opposite of catabolic processes. Anabolic processes refer to the processes of creating cells and tissues, as well as substances necessary for the functioning of the body. Regenerative processes and anabolism of muscle tissue largely depend on the level of growth hormone, insulin and testosterone in the blood plasma. Physical activity significantly increases the concentration of many hormones in the blood plasma, and not only immediately during exercise. From the beginning of exercise (for example, close to maximum power), in the first 4-10 minutes, the concentration of various hormones and metabolic products changes spontaneously. Thus, with the start of exercise, the concentration of lactic acid in the blood increases. And the concentration of glucose begins to change inversely with the concentration of lactic acid. The level of somatotropin in the blood increases with the increase in the time of physical exercise.